Attitudes towards non‐invasive prenatal diagnosis among obstetricians in Pakistan, a developing, Islamic country. (10th February 2017) - Ahmed, Shenaz; Jafri, Hussain; Rashid, Yasmin; Mason, Gerald; Ehsan, Yasmin; Ahmed, Mushtaq
Abstract: Objectives: Stakeholders' views are essential for informing implementation strategies for non‐invasive prenatal testing (NIPT). Little is known about such views in developing countries. We explored attitudes towards NIPT among obstetricians in Pakistan, a developing, Islamic country. Methods: A 35‐item questionnaire was distributed and collected at eight events (a national conference and seven workshops in five cities) for obstetric professionals on advances in fetal medicine. Results: Responses from 113 obstetrician show positive attitudes towards implementation of NIPT: 95% agreed prevention of genetic conditions was a necessity, and 97% agreed public hospitals should provide prenatal screening tests. However, participants also agreed the availability of NIPT would increase social pressure on women to have prenatal screening tests and to terminate an affected pregnancy (53% and 63%, respectively). Most participants would not offer NIPT for sex determination (55%), although 31% would. The most valued aspects of NIPT were its safety, followed by its utility and then accuracy. Conclusion: Participants generally supported the implementation of NIPT but raised concerns about social implications. Therefore, national policy is needed to regulate the implementation of NIPT, and pretest information and post‐test genetic counselling are needed to mitigate social pressure and support parents to make informed decisions. © 2017 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Non‐invasive prenatal testing (NIPT) is being introduced into private prenatal health care in developing countries. Stakeholders' views are essential for informing implementation strategies for NIPT. Little is known about stakeholders' views in developing countries. What does this study add? There is a need for a national policy on prenatal screening to regulate the implementation of NIPT. Pretest information and post‐test genetic counselling are essential to help mitigate social pressure and support parents to make informed decisions.